2022
DOI: 10.1093/aje/kwab293
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Trends of COVID-19 Vaccine Hesitancy and Vaccine Uptake in a National Cohort of US Adults: A Longitudinal Study

Abstract: We estimated the trends and correlates of vaccine hesitancy, and its association with subsequent vaccine uptake among 5,458 adults in the United States. Participants belonged to the CHASING COVID Cohort, a national longitudinal study. Trends and correlates of vaccine hesitancy were examined longitudinally in eight interview rounds from October 2020 to July 2021. We also estimated the association between willingness to vaccinate and subsequent vaccine uptake through July 2021. Vaccine delay and refusal decrease… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 33 publications
10
48
0
Order By: Relevance
“…However, having comorbidities was found to predict vaccine uptake in a US cohort, suggesting that associations may be mixed. 25 Consistent with our findings, a history of annual influenza vaccine inoculations has generally been found to predict vaccine uptake and persistent vaccine willingness, 16,22 though one study has found evidence to support the opposite conclusion among a population of those living with multiple sclerosis. 23 Those with annual influenza vaccine routines may have stronger faith in the benefits of vaccines, predisposing them to remain vaccine willing in the face of misinformation and mass reporting of adverse effects.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…However, having comorbidities was found to predict vaccine uptake in a US cohort, suggesting that associations may be mixed. 25 Consistent with our findings, a history of annual influenza vaccine inoculations has generally been found to predict vaccine uptake and persistent vaccine willingness, 16,22 though one study has found evidence to support the opposite conclusion among a population of those living with multiple sclerosis. 23 Those with annual influenza vaccine routines may have stronger faith in the benefits of vaccines, predisposing them to remain vaccine willing in the face of misinformation and mass reporting of adverse effects.…”
Section: Discussionsupporting
confidence: 88%
“…22 A study of refugees living in the US and presenting for COVID-19 testing found that 19¢ 3% of those initially desiring vaccination changed their mind by follow-up four months later. 20 Our findings are comparable to the Asian-specific proportion reported by Rane et al (2021) (4¢8% vs 6¢0%), 25 whereas short followup periods and studies of limited, non-nationally representative subpopulations limit reasonable comparisons with the remaining research. That our findings resemble those in the US Asian population suggest that underlying cultural factors may play a role in determining the propensity to reverse vaccine willingness.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Arce et al, 2021 , Brown et al , Carson, 2021 , Chen and Krieger., 2021 , Kazemian et al, 2021 , Latkin et al, 2021 , Liao and De Maio., 2021 , Liu and GabrielLi, 2021 , Mollalo and Tatar, 2021 , Phelan and Bruce, 2015 , Rane et al, 2022 , Salomon et al, 2021 , Siegel et al, 2021 , Tal et al, 2020 , Willis et al, 2022 , Wright et al, 2014 …”
Section: Uncited Referencesmentioning
confidence: 99%